HUBUNGAN ANTARA KONFORMITAS DAN HARGA DIRI DENGAN KECENDERUNGAN AGRESIVITAS REMAJA - Ariswanti Triningtyas, Diana; Pratikto, Herlan; Suroso, Suroso (Jurnal Pendidikan, 2013)
The study examined the relationship of conformity, self-esteem, and aggressiveness. Research subjects were 76 middle adolescents ages 16 to 18 years (16 males and 22 females). Data of aggressiveness obtained from the aggressiveness scale. Data of conformity obtained from the conformity scale. Data of self-esteem obtained from self-esteem scale. The results of regression analysis of conformity and self-esteem R = 0.325, F = 2.130, p = 0.126 (p> 0.01). Conformity and self-esteem variables simultaneously is not associated with adolescent aggressiveness. The results of partial conformity test t = -1.888, p = 0.063 (p> 0.05). Conformity variables in isolation is not related to aggressiveness. The results of partial self-test t = -1.061, p = 0.292 (p> 0.05). Variable self-esteem in isolation is not related to aggressiveness.Keywords: aggression, conformity, self-esteem